2021
DOI: 10.1002/art.41605
|View full text |Cite
|
Sign up to set email alerts
|

Synovial Fluid Neutrophils From Patients With Juvenile Idiopathic Arthritis Display a Hyperactivated Phenotype

Abstract: Objective. Juvenile idiopathic arthritis (JIA) is the most common rheumatic disease in childhood. The predominant subtypes, oligoarticular and polyarticular JIA, are traditionally considered to be autoimmune diseases with a central role for T cells and autoantibodies. Mounting evidence suggests an important role for neutrophils in JIA pathogenesis. We undertook this study to investigate the phenotypic features of neutrophils present in the blood and inflamed joints of patients.Methods. JIA synovial fluid (SF) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 46 publications
0
23
0
Order By: Relevance
“…Children with oligoarticular JIA present with persistent, unexplained and often asymmetric arthritis in one to four joints before the age of sixteen, often associated with anti-nuclear autoantibodies (13). We and others have shown that neutrophils in synovial fluid from children with oligoarticular JIA are activated and express atypical neutrophil surface markers (2,5). JIA synovial fluid neutrophils also have impaired phagocytosis and trend towards impaired oxidative burst compared to circulating neutrophils, related to the phenotype shift (2).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Children with oligoarticular JIA present with persistent, unexplained and often asymmetric arthritis in one to four joints before the age of sixteen, often associated with anti-nuclear autoantibodies (13). We and others have shown that neutrophils in synovial fluid from children with oligoarticular JIA are activated and express atypical neutrophil surface markers (2,5). JIA synovial fluid neutrophils also have impaired phagocytosis and trend towards impaired oxidative burst compared to circulating neutrophils, related to the phenotype shift (2).…”
Section: Introductionmentioning
confidence: 91%
“…Swollen and painful joints are characteristics of many autoimmune rheumatic diseases. In several of these diseases, neutrophils in synovial fluid of inflamed joints have been found to have altered phenotype and behavior, driving local inflammation (1)(2)(3)(4)(5). Neutrophils are not only pro-inflammatory mediators but also immunoregulators, where one of their immunoregulatory effects is the capacity to suppress T cell proliferation and cytokine production (6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms of immunopathogenesis of JIA are still poorly understood. JIA categories are complex, heterogeneous, with different contributions of immune system players and effector cells ( 24 , 25 , 58 63 ). Indeed, several studies have demonstrated a predominance of adaptive immunity in the pathogenesis of oJIA, pJIA, ERA, and JPsA ( 14 , 17 , 18 , 24 , 25 , 39 , 57 , 64 – 86 ), whereas innate immune responses are the major contributors to disease development and progression in sJIA ( 29 , 59 , 87 98 ).…”
Section: Immunopathogenesis Of Juvenile Idiopathic Arthritismentioning
confidence: 99%
“…Additionally, neutrophils express a functionally active membrane-bound RANKL, the ligand for receptor activator of NF-kB (RANK) and so can activate osteoclastogenesis ( 202 ). In the joints of JIA patients, activated neutrophils were abundantly present ( 203 205 ) and the presence of S100A12 in synovial fluids from JIA patients ( 189 ) provides evidence for their involvement in disease pathogenesis.…”
Section: Emergency Granulopoiesis In Sjiamentioning
confidence: 99%
“…Whereas one study failed to show an increased number of hypersegmented neutrophils, another study showed, by imaging cytometry, that patients with systemically active disease have increased numbers of hypersegmented neutrophils ( 149 , 184 ). We recently uncovered neutrophil-DC hybrid cells (expressing both neutrophil and DC markers) in the synovial fluid from patients with JIA ( 205 ) that may serve as antigen-presenting cells ( 209 , 210 ), eventually contributing to the arthritic phenotype. Remarkably, neutrophil protease genes (including MMP-8 , and MMP-9 ) could also be found in PBMC microarray datasets of sJIA patients and might reflect the presence of low-density granulocytes in the PBMC fraction, which was confirmed by flow cytometry analysis ( 185 ).…”
Section: Emergency Granulopoiesis In Sjiamentioning
confidence: 99%